Association of Rhesus Blood Group (RhD) and Toxoplasmosis in Women with Miscarriage in Erbil - Banaz Sadik Smael; Sadiya Abdulla Palpitany; Kazhal Hassan Hama Rahim (Hawler Medical University, 2018)
Background and objective: Toxoplasmosis has worldwide distribution and the incidence of the disease varies around the world. Human blood is categorized within two main systems: ABO and Rhesus factor blood group systems. The Rhesus factor protein which is the Rhesus factor gene product and a major component in the Rh blood group system carries the strongest blood group immunogen, This study aimed to estimate the sero-prevalence of toxoplasmosis and to investigate the distribution of ABO and Rhesus factor blood groups among women with toxoplasma infection. Methods: This cross-sectional study was carried out in Erbil from September 2017 to April 2018, in which 200 women with history of abortion were enrolled. Blood samples were collected and tested for anti-toxoplasma IgM antibody using direct agglutination and enzyme linked immunosorbent assay techniques. Results: the percentages of anti-toxoplasma IgM was 33.5% .and 65 (97%) of the seropositive women were RhD negative. Significant relationship between RhD blood group and Toxoplasma seropositive was observed while no significant relationship was found between toxoplasmosis and each ABO phenotype and demographic characteristics. Comparably, high sero-prevalence rate of anti-toxoplasma antibody was found among age group 21-40 years old (73.1%), however, it was statistically non- significant. Conclusion: Anti toxoplasma IgM antibodies was relatively high among women with history of abortion in Erbil and Rhesus factor positive was significant.